Pelatihan Pembuatan Produk Kimia Terapan: Pembuatan Pelembut Pakaian bagi Siswa-Siswi SMAN 1 Cepiring Kabupaten Kendal: Pelatihan Pembuatan Produk Kimia Terapan: Pembuatan Pelembut Pakaian bagi Siswa-Siswi SMAN 1 Cepiring Kabupaten Kendal - Herman, Herman Yoseph Sriyana (Fakultas Komputer dan Pendidikan Universitas Ngudi Waluyo, 2025)
SMA Negeri 1 Cepiring Kendal is located at Jl. Sri Agung No 57, Sembung, Cepiring, Kec. Kendal, Jawa Tengah, 51352. SMA Negeri 1 Cepiring Kendal has the slogan BE CREATIVE, namely Collaboration, Religion, and Art. SMA Negeri 1 Cepiring vision is to create students who have noble morals, are independent, creative, and have an environmental perspective. One of the means to realize the nature and creative attitude of SMA Negeri 1 students is by holding training on the manufacture of applied chemical products. The presence of the D3 Chemical Engineering Polteka Mangunwijaya community service team aims to open students' insights about the types, principles, and methods of making applied chemical products. One of the applied chemical products that is easy to make is a softener. The way to use softener is to dissolve it in water and then use it to soak clothes. The method used in this training activity is divided into 3 main sessions, including: classical explanations, product manufacturing practices, and question and answer sessions. The result of this activity is the enthusiasm of SMA Negeri 1 Cepiring students in understanding and practicing the softener manufacturing process. Knowledge of tools and materials, principles, and methods of making softener is expected to increase students' creativity in developing other applied chemical products. Keywords: pelembut pakaian; students; training